2020
DOI: 10.3390/ma13143223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics as a Means to Investigate Grain Size and Strain Rate Effect on Plastic Deformation of 316 L Nanocrystalline Stainless-Steel

Abstract: In the present study, molecular dynamics simulations were employed to investigate the effect of strain rate on the plastic deformation mechanism of nanocrystalline 316 L stainless-steel, wherein there was an average grain of 2.5–11.5 nm at room temperature. The results showed that the critical grain size was 7.7 nm. Below critical grain size, grain boundary activation was dominant (i.e., grain boundary sliding and grain rotation). Above critical grain size, dislocation activities were dominant. There was a sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, bigger grain size offers low resistance to fatigue reaching the plastic deformation region. 22 Hall–Petch equation 23 shows the association between yield strength and the grain diameter (equation (4))where σy is yield stress, d is grain diameter, σ0 is stress upon the friction and k refers to a constant coefficient. 23 Based on this equation, increasing the grain diameter would end up in decreasing the yield stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bigger grain size offers low resistance to fatigue reaching the plastic deformation region. 22 Hall–Petch equation 23 shows the association between yield strength and the grain diameter (equation (4))where σy is yield stress, d is grain diameter, σ0 is stress upon the friction and k refers to a constant coefficient. 23 Based on this equation, increasing the grain diameter would end up in decreasing the yield stress.…”
Section: Methodsmentioning
confidence: 99%
“…However, bigger grain size offers low resistance to fatigue reaching the plastic deformation region. 22 Hall-Petch equation 23 shows the association between yield strength and the grain diameter (equation ( 4))…”
Section: Grain Sizementioning
confidence: 99%
“…As the dislocation density of cavitation-peened stainless steel was also smaller than that of shot peening at equivalent compressive residual stress conditions, it was found that this is one of reasons why the relaxation of cavitation peening is less than that of shot peening. It was also reported by using tensile testing that the yield stress of stainless steel increased from 6% to 8% with increasing high strain rate [24][25][26][27]. Cavitation peening is a kind of shockwave process that occurs at bubble collapse; thus, the strain rate of cavitation peening is larger than that of shot peening.…”
Section: Introductionmentioning
confidence: 99%
“…The main deformation mechanisms of small-sized grains are grain boundary sliding, grain boundary rotation, and partial dislocations, while the main deformation mechanisms of large-sized grains are extended dislocations and grain boundary rotation. Abdelrahim Husain et al [9,10] studied the mechanical properties of nanocrystalline 316 L stainless steel under tensile load and the effect of strain rate on the plastic deformation mechanism of stainless steel, the main deformation mechanisms of polycrystals are deformation twinning and extended dislocations when grain size is larger than the critical average grain size, and the main deformation mechanisms of polycrystals are grain boundary sliding and grain rotation when the grain size is smaller than the critical average grain size.…”
Section: Introductionmentioning
confidence: 99%